Development and characterization of an immunochromatographic test for the rapid diagnosis of Talaromyces (Penicillium) marneffei - Kritsada Pruksaphon (2018)
© 2018 Pruksaphon et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Talaromyces (Penicillium) marneffei is a thermally dimorphic fungus that can cause opportunistic systemic mycoses in patients infected with the human immunodeficiency virus (HIV). It has also been reported among patients with other causes of immunodeficiency, such as systemic lupus erythematosus, cancer, organ transplanted patients receiving immunosup-pressive drug and adult onset immunodeficiency syndromes. Recent studies indicate that the clinical manifestations, laboratory findings and treatment strategies of talaromycosis (penicilliosis) marneffei are different between patients with and without HIV infection. Therefore early and accurate diagnosis of talaromycosis marneffei is crucial to the proper management and treatment. Since current diagnostic methods are currently inadequate, the aim of this study was to develop an immunochromatographic test (ICT) for the detection of T. marneffei yeast antigens in urine samples. The highly T. marneffei-specific monoclonal antibody 4D1 (MAb 4D1) conjugated with gold colloid at pH 6.5 was used as signal generator. The nitrocellulose membrane was lined with T. marneffei cytoplasmic yeast antigen (TM CYA) to serve as the test line, and rabbit anti-mouse IgG was the control line. Subjecting the assembled test strip to urine samples containing T. marneffei antigen produced a visible result within 20 minutes. The sensitivity limit of the assay was 3.125μg/ml of TM CYA. The ICT was used to test urine samples from 66 patients with blood culture confirmed talaromycosis marneffei, 42 patients with other fungal or bacterial infections, and 70 normal healthy individuals from endemic area of T. marneffei. The test exhibited sensitivity, specificity and accuracy of 87.87%, 100% and 95.5%, respectively. This rapid, user-friendly test holds great promise for the serodiagnosis of T. marneffei infection.